Virginia Woolf and heritage : selected papers from the twenty-sixth Annual International Conference on Virginia Woolf - De Gay, Jane, 1966-; Breckin, Tom; Reus, Anne (Clemson University Press, 2017)
This book brings together an international team of world-class scholars to explore how Woolf engaged with heritage, how she understood and represented it, and how she has been represented by the heritage industry.